Evaluation of Deese-Roediger-McDermott paradigm in Serbian matherials and subject sample - Purić, Danka; Lalović, Dejan (Primenjena psihologija, 2010)
’False memories’ is a term used to denote contents recalled but never learned or experienced in situation recalling is reffered to. In the introductory section of the paper we begin by examining the significance of false memory fenomena for various applied psychology fields. Afterwards we focus on associative false memories of Deese-Roediger-McDermott type (DRM) as on the false memory phenomenon sharing most of the other false memories phenomena significant properties, while being relatively easy to demonstrate using everyday words. In following sections we present results of our initial research on DRM false memories in Serbian subject and language sample. The research was conducted in student sample (N = 121) by employing 14 lists of 15 associatively connected words. Lists were chosen among materials from English normative study, translated and minimally adapted. Main finding is that all the lists evoked false memories, proportions of which ranged .2 - .37. Similar range of DRM false memories proportion was reported in English and other languages. Rank correlation of .58 between Serbian and correspondent English lists with respect to the proportion of false memories evoked further suggest DRM false memories to be a robust phenomenon, relatively independent of language and subject sample employed. Our data lend support to the Activation/monitoring theory as to the most prominent account of associative false memories creation mechanisms. We conclude by offering suggestions for the Serbian materials improvement and by outlining possible directions in further research of the phenomenon which was under scrutiny.